Memory Authentication using Soft PUFs (International Journal of Engineering and Computer Science, 2014)
Physical Unclonable Functions (PUFs) are circuits that exploit chip-unique features to be used as signatures which can be used as good silicon biometrics. These signatures are based on semiconductor fabrication variations that are very difficult to control or reproduce. These chip-unique signatures together with strong challenge-response authentication algorithm can be used to identify and secure chips. This paper expands the security avenues covered by PUF and FPGAs by introducing a new class of concept called “Soft PUFs.” We propose robust challenge- response authentication solution based on a PUF device that provides stronger security guarantees to the user than what previously could be achieved. By exploiting the silicon uniqueness of each FPGA device and incorporating a special authentication algorithms in existing FPGA fabric, FPGAs, embedded systems can be used for new security-oriented and network- oriented applications that were not previously possible or thought of.